Effect of clinical guidelines in nursing, midwifery, and the therapies: a systematic review of evaluations. Issue 4 (December 1998) - Thomas, L H; McColl, E; Cullum, N; Rousseau, N; Soutter, J; Steen, N
Abstract : BACKGROUND: Although nursing, midwifery, and professions allied to medicine are increasingly using clinical guidelines to reduce inappropriate variations in practice and ensure higher quality care, there have been no rigorous overviews of their effectiveness, 18 evaluations of guidelines were identified that meet Cochrane criteria for scientific rigor. METHODS: Guideline evaluations conducted since 1975 which used a randomised controlled trial, controlled before and after, or interrupted time series design were identified through a combination of database and hand searching. RESULTS: 18 studies met the inclusion criteria. Three studies evaluated guideline dissemination or implementation strategies, nine compared use of a guideline with a no guideline state; six studies examined skill substitution: performance of nurses operating according to a guideline were compared with standard care, generally provided by a physician. Significant changes in the process of care were found in six out of eight studies measuring process and in which guidelines were expected to have a positive impact on performance. In seven of the nine studies measuring outcomes of care, significant differences in favour of the intervention group were found. Skill substitution studies generally supported the hypothesis of no difference between protocol driven by nurses and care by a physician. Only one study included a formal economic evaluation, with equivocal findings. CONCLUSIONS: Findings from the review provide some evidence that care driven by a guideline can be effective in changing the process and outcome of care. However, many studies fell short of the criteria of the Cochrane Effective Practice and Organisation of Care Group (EPOC) for methodological quality.